Transesophageal Echocardiography Assisting in the Diagnosis of Intraabdominal Hemorrhage During Cardiac Arrest. Issue 7 (1st April 2016) - Jelly, Christina Anne; Jiang, Yandong; Hoeft, Mark; Liang, Yafen
Abstract : Transesophageal echocardiography (TEE) has been frequently used to identify potential etiologies of intraoperative cardiac arrest for noncardiac surgical patients. However, rescue TEE to assist in the diagnosis of intraabdominal hemorrhage has never been reported. We present a patient who developed cardiac arrest on emergence after an elective abdominal surgery. Intraoperative TEE revealed hypovolemia with hyperdynamic left and right ventricles. It also demonstrated a 3.3- by 13.2-cm circular perihepatic fluid collection on transgastric views raising concern for major intraabdominal hemorrhage as the cause for the cardiac arrest. This prompted surgical reexploration, which confirmed the diagnosis. We suggest that transgastric views to identify intraabdominal fluid collections should be considered during a rescue TEE if intraabdominal hemorrhage is suspected. Abstract : Supplemental Digital Content is available in the text.